Scratching the surface of Afrotropical Dissomphalus (Hymenoptera, Bethylidae): a revision uncovering 114 new species - Colombo, Wesley D.; Brito, Chirlei D.; Azevedo, Celso O. (Zootaxa, 2024)
The main goal of this paper is to revise the Dissomphalus genus within the Afrotropical region. Specimens were collected across seventeen countries: Benin, Botswana, Cameroon, Central African Republic, Democratic Republic of Congo, Gabon, Guinea, Kenya, Mozambique, Namibia, Nigeria, Rwanda, South Africa, Tanzania, Uganda, Zambia and Zimbabwe. A total of 127 species have been identified in the Afrotropical region. Thirteen of these species have been previously described, namely: D. adscitus Benoit, D. alberti Benoit, D. babaeculus (Benoit), D. clibanarius Benoit, D. crucialis Benoit, D. forchhammeri (Krombein), D. globiceps Benoit, D. indeceptilis Benoit, D. matticus (Benoit), D. nicaeus Benoit, D. prophylax Benoit, D. rwindianus Benoit and D. tridentatus (Kieffer). Additionally, we propose D. kiefferi Benoit syn. nov. as a junior synonym of D. matticus and D. orophilus Benoit syn. nov. as a junior synonym of D. adscitus. Furthermore, this study introduces 114 new species for the Afrotropical region. We also provide an updated key for both females and males in this region.